2019
DOI: 10.1155/2019/3013716
|View full text |Cite
|
Sign up to set email alerts
|

Remifentanil Protects against Lipopolysaccharide-Induced Inflammation through PARP-1/NF-κB Signaling Pathway

Abstract: Sepsis is a leading cause of death in patients with severe infection worldwide. Remifentanil is an ultra-short-acting, potent opioid analgesic. In the study, we aimed to investigate the role and underlying mechanism of remifentanil in lipopolysaccharide- (LPS-) induced inflammation in human aortic endothelial cells (HAECs). HAECs were pretreated with phosphate-buffered saline (PBS) or remifentanil (2.5 μM) for 30 min, then stimulated by LPS (10 μg/ml) for another 24 h. Poly(ADP-ribose) polymerase 1 (PARP-1) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…Remifentanil was an ultra-short-acting, potent opioid analgesic. Previous studies showed that remifentanil could attenuate inflammation and acute lung injury through signaling pathway [41,42]. So, in our study, the lower occurrence of PPCs in DEX group might be in connection with the lessened amount of remifentanil.…”
Section: Placebo Group Referencesupporting
confidence: 56%
“…Remifentanil was an ultra-short-acting, potent opioid analgesic. Previous studies showed that remifentanil could attenuate inflammation and acute lung injury through signaling pathway [41,42]. So, in our study, the lower occurrence of PPCs in DEX group might be in connection with the lessened amount of remifentanil.…”
Section: Placebo Group Referencesupporting
confidence: 56%
“…RTF attenuates lipopolysaccharide-induced acute lung injury by downregulating the NF-κB signaling pathway (56). RTF reduces LPS-induced inflammatory response through PARP-1/NF-κB signaling pathway in human aortic endothelial cells (HAECs) (57). In this research, RFT alleviated PTO injury by inhibiting the phosphorylation of PI3K/AKT/NF-κB p65 in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 77%
“…Remifentanil was an ultra-short-acting, potent opioid analgesic. Previous studies showed that remifentanil could attenuate inflammation and acute lung injury through signaling pathway 42,43 . So, in our study, the lower occurrence of PPCs in DEX group might be in connection with the lessened amount of remifentanil.…”
Section: Discussionmentioning
confidence: 99%